2022
DOI: 10.1029/2022jg007055
|View full text |Cite
|
Sign up to set email alerts
|

Wildfires Temperature Estimation by Complementary Use of Hyperspectral PRISMA and Thermal (ECOSTRESS & L8)

Abstract: This paper deals with detection and temperature analysis and of wildfires using PRISMA imagery. Precursore IperSpettrale della Missione Applicativa (Hyperspectral Precursor of the Application Mission, PRISMA) is a new hyperspectral mission by ASI (Agenzia Spaziale Italiana, Italian Space Agency) launched in 2019. This mission provides hyperspectral images with a spectral range of 400–2,500 nm and an average spectral resolution less than 12 nm and a spatial resolution of 30 m/pixel. This study focuses on the wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…PRISMA acquisition was planned under very urgent acquisition (within the project "Progetto per Sviluppo di prodotti iperspettrali prototipali evoluti" Rif: CMM-PRO-18-013, funded by Italian Space Agency) aiming to map the fire front on the region, but the large fire was suppressed at the time of PRISMA acquisition (Figure 4). However, three hot spots were detected by using the Hyperspectral Fire Detection Index (HFDI) [29,43,44], and verified during the manual inspection of the pixels spectrum, by using both the NIR-SWIR color composition and spectral behaviour of active fires' reflectance. The presence of clouds and water are evident in this area, which has been utilized for training the CNN in detecting and distinguishing between these two categories; meanwhile, the three hot spots corresponding to small pastoral fires were excluded from the dataset; they were utilized to validate the generalization ability assessment process, i.e., to verify if the CNN trained on Australia fires can also successfully detect the small fires in Sicily.…”
Section: Sicily Italymentioning
confidence: 99%
See 1 more Smart Citation
“…PRISMA acquisition was planned under very urgent acquisition (within the project "Progetto per Sviluppo di prodotti iperspettrali prototipali evoluti" Rif: CMM-PRO-18-013, funded by Italian Space Agency) aiming to map the fire front on the region, but the large fire was suppressed at the time of PRISMA acquisition (Figure 4). However, three hot spots were detected by using the Hyperspectral Fire Detection Index (HFDI) [29,43,44], and verified during the manual inspection of the pixels spectrum, by using both the NIR-SWIR color composition and spectral behaviour of active fires' reflectance. The presence of clouds and water are evident in this area, which has been utilized for training the CNN in detecting and distinguishing between these two categories; meanwhile, the three hot spots corresponding to small pastoral fires were excluded from the dataset; they were utilized to validate the generalization ability assessment process, i.e., to verify if the CNN trained on Australia fires can also successfully detect the small fires in Sicily.…”
Section: Sicily Italymentioning
confidence: 99%
“…Our earlier studies have demonstrated the potential for artificial intelligence, on-board computing, and satellite constellations to serve as interconnected components for future services that should aid in monitoring and prompt responses to wildfire events. The quality of the information that can be extracted from PRISMA HS imagery was investigated in [29], where analytical methodologies were proposed to locate wildfires and estimate the temperature of active fire pixels. At the same time, we showed the possibility of implementing Trusted Autonomous Satellite Operations [30][31][32] by utilizing artificial intelligence [33,34] on-board satellites with astrionics for data processing [35][36][37].…”
Section: Introductionmentioning
confidence: 99%